2012
DOI: 10.4321/s0213-61632012000400001
|View full text |Cite
|
Sign up to set email alerts
|

Profile of male adolescents with conduct disorder on intellectual efficacy, cognitive flexibility, cognitive coping, impulsivity and alexithymia: A comparison with high-risk controls

Abstract: -Background and Objectives: To specify which of the documented cognitive and emotional deficits characterize adolescents with conduct disorder (CD) compared with high-risk controls.Methods: High-risk adolescent males with and without CD were compared on intellectual efficiency, cognitive flexibility, impulsivity, alexithymia, and cognitive coping strategies. Substance use was controlled for in analyses.Results: Both groups showed normal intellectual efficiency and cognitive flexibility, as well as heightened a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
0
5
0
1
Order By: Relevance
“…Furthermore, emotion regulation predicts negatively externalizing problems in adolescence (Batum & Yagmurlu, 2007;McLaughlin et al, 2011). In the same line of research, Pihet et al (2012) showed that adolescents exhibiting externalizing symptoms have emotional regulation deficits such as difficulties recognizing and describing their feelings. Similarly, Garnefski et al (2005) reported that compared to youths with externalizing problems, adolescents with internalizing problems tend to use more dysfunctional cognitive emotion regulation strategies such as self-blame, rumination and lack of positive reappraisal.…”
Section: Emotion Regulationmentioning
confidence: 99%
“…Furthermore, emotion regulation predicts negatively externalizing problems in adolescence (Batum & Yagmurlu, 2007;McLaughlin et al, 2011). In the same line of research, Pihet et al (2012) showed that adolescents exhibiting externalizing symptoms have emotional regulation deficits such as difficulties recognizing and describing their feelings. Similarly, Garnefski et al (2005) reported that compared to youths with externalizing problems, adolescents with internalizing problems tend to use more dysfunctional cognitive emotion regulation strategies such as self-blame, rumination and lack of positive reappraisal.…”
Section: Emotion Regulationmentioning
confidence: 99%
“…The exclusion criteria was: lifetime presence of psychotic disorders, insufficient reasoning ability assessed using the Raven Matrices test [35]. The Conduct Disorder (CD) dimension was assessed with the Pedersen questionnaire for CD [36], the same way it was successfully done in Pihet, Suter [37]. The questionnaire has a cut-off allowing us to discriminate between youths with or without CD.…”
Section: Ethical Considerationmentioning
confidence: 99%
“…In children and adolescents, functional difficulties associated with impulsive behaviors (e.g., emotional dysregulation, difficulties managing social relations) are pervasive in numerous psychological disorders, such as pathological video game use (Gentile et al, 2011) or conduct disorders (Pihet, Suter, Halfon, & Stephan, 2012). However, contrary to what has been observed in adults, few studies have examined children’s impulsive behaviors according to the UPPS model (e.g., Marmorstein, 2013; Zapolski & Smith, 2013; Zapolski, Stairs, Fried Settles, Combs, & Smith, 2010).…”
mentioning
confidence: 99%